Amino-terminated biphenylthiol self-assembled monolayers as highly reactive molecular templates - Meyerbröker, Nikolaus; Waske, Prashant Ankushrao; Zharnikov, Michael (The journal of chemical physics, 2015)
Self-assembled monolayers (SAMs) with amino tail groups are of interest due to their ability of coupling further compounds. Such groups can be, in particular, created by electron irradiation of nitro- or nitrile-substituted aromatic SAMs, which provide a basis for chemical nanolithography and the fabrication of functionalized nanomembranes. An estimate of reactivity of the created amino groups requires a reference system of homogeneous, amino-terminated aromatic SAMs, which can also be used as a highly reactive molecular template. Here, we describe the synthesis of 4′-aminobiphenyl-4-thiol (ABPT) and SAMs prepared from this precursor on Au(111). The monolayers were characterized by X-ray photoelectron spectroscopy and near edge X-ray absorption fine structure spectroscopy, which revealed that they are well defined, chemically uniform, densely packed, and highly ordered. To examine the influence of electron irradiation on the reactivity of the terminal amino groups, ABPT SAMs were exposed to low energy (50 eV) electrons up to a dose of 40 mC/cm2 and, subsequently, immersed in either trifluoroacetic, pentafluoropropionic, or heptafluorobutyric anhydride. Analysing the amount of the attached anhydride species made it possible to determine the percentage of reactive amino groups as well as the effect of steric hindrance upon the coupling reaction. The above results are compared with those obtained for the well-established nitro-substituted biphenylthiol monolayers.
Gesehen am 29.05.2020